Activity of Voriconazole, a New Triazole, Combined with Neutrophils or Monocytes against Candida albicans: Effect of Granulocyte Colony-Stimulating Factor and Granulocyte-Macrophage Colony-Stimulating Factor - Vora, Shefali (American Society for Microbiology, 1998)
The antifungal activity of voriconazole (VCZ) was tested against Candida albicans in the absence or presence of polymorphonuclear neutrophils (PMN) or monocytes. In some experiments, VCZ was compared to fluconazole (FCZ). On a weight basis, VCZ was 10-fold more efficacious than FCZ against C. albicans Sh27. Against an FCZ-resistant isolate, VCZ at 1 μg/ml produced the same fungistasis as FCZ at 20 μg/ml. VCZ at 0.1 μg/ml collaborated with PMN for enhanced killing to the same extent as FCZ at 1.0 μg/ml. Granulocyte-colony-stimulating factor (G-CSF) enhanced the candidacidal activity of PMN, and it increased the collaboration of PMN with VCZ for killing. Granulocyte-macrophage (GM)-CSF also significantly enhanced both the killing by PMN and the collaboration of PMN with VCZ for killing. VCZ collaborated with monocytes for enhanced killing of C. albicans Sh27, and GM-CSF increased this collaboration. Taken together, these data show that VCZ is more potent than FCZ against C. albicans isolates, alone and in collaboration with PMN or monocytes for enhanced killing. In addition, G-CSF- or GM-CSF-activated PMN and monocytes have enhanced collaboration with VCZ compared to that of unstimulated phagocytes with VCZ.